A new insight on the variation of the electric conductivity and conductive network of silver-coated glass particles/silicone elastomer composites under tensile strain. (18th November 2016) - Ning, Nanying; Miao, Chunmeng; Zou, Hua; Shao, Qian; Wang, Sishu; Zhang, Liqun; Tian, Ming
Abstract: In this study, we introduced silver-coated glass particles (SG) into methyl vinyl silicone rubber (PMVS) matrix to prepare conductive elastomeric composites (CECs) with high electrical conductivity. The effect of the content of SG, the tensile strain and the stretch-recovery cycle times on the conductivity of CECs were studied. Interestingly, the conductivity of all the composites obviously increases with the increase in the applied tensile strain or the stretch-recovery cycle times to certain degree, different from that reported in many previous studies. The reason is that the dispersion of SG in PMVS matrix becomes more nonuniform with the increase in tensile strain, and the redistribution of SG in matrix results in the formation of much more new conductive network. On the other hand, the change in conductivity of the composites with the content of SG just exceeding the percolation threshold is much more significant than that with the content of SG far exceeding the percolation threshold. This is attributed to the more perfect conductive network in the composites with higher content of SG. The relationship between the conductivity and conductive filler network of SG/PMVS composites were clarified. This study provides guidance for the preparation and application of high performance CECs with excellent conductivity and stability of conductivity. Graphical abstract: